Anti-Cancer, Pharmacokinetic and Biodistribution Studies of Cremophor EL Free Alternative Paclitaxel Formulation - K. Jain, Subheet; Utreja, Puneet; K. Tiwary, Ashok; Mahajan, Mohit; Kumar, Nikhil; Roy, Partha (Current Drug Safety, 2014)
Purpose: The aim of the present investigation is to determine the in vivo potential of previously developed and optimized Cremophor EL free paclitaxel (CF-PTX) formulation consisting of soya phosphatidylcholine and biosurfactant sodium deoxycholate. CF-PTX was found to have drug loading of 6 mg/ml similar to Cremophor EL based marketed paclitaxel formulation. In the present study, intracellular uptake, repeated dose 28 days sub-acute toxicity, anti-cancer activity, biodistribution and pharmacokinetic studies were conducted to determine in vivo performance of CF-PTX formulation in comparison to marketed paclitaxel formulation. Methods: Intracellular uptake of CF-PTX was studied using A549 cells by fluorescence activated cell sorting assay (FACS) and fluorescence microscopy. In vivo anti-cancer activity of CF-PTX was evaluated using Ehrlich ascites carcinoma (EAC) model in mice followed by biodistribution and pharmacokinetic studies. Results: FACS investigation showed that fluorescence marker acridine orange (AO) solution showed only 19.8±1.1% intracellular uptake where as significantly higher uptake was observed in the case of AO loaded CF-PTX formulation (85.4±2.3%). The percentage reduction in tumor volume for CF-PTX (72.5±2.3%) in EAC bearing mice was found to be significantly (p<0.05) higher than marketed formulation (58.6±2.8%) on 14th day of treatment. Pharmacokinetic and biodistribution studies showed sustained plasma concentration of paclitaxel depicted by higher mean residence time (MRT; 18.2±1.8 h) and elimination half life (12.8±0.6 h) with CF-PTX formulation as compared to marketed formulation which showed 4.4±0.2 h MRT and 3.6±0.4 h half life. The results of the present study demonstrated better in vivo performance of CF-PTX and this formulation appears to be a promising carrier for sustained and targeted delivery of paclitaxel.
Keywords: pharmacokinetic study